Pharmacological activities of coral reef associated actinomycetes, Saccharopolyspora sp. IMA1. (September 2020) - Krishnamoorthy, Madhuri; Dharmaraj, Divya; Rajendran, Kumar; Karuppiah, Kannan; Balasubramanian, Malaikozhundan; Ethiraj, Kannapiran
Abstract: Emergence of multidrug resistance among the aquatic pathogens enhances the demand for new antimicrobial compounds to replace currently using antibiotics in order to overcome resistance using microorganisms. The main scope of the present study was to isolate a potential antagonistic actinobacteria and appraise their antibacterial, antioxidant and anticancer properties for its therapeutic prospective . In the primary screening, the isolates were tested against aquatic bacterial pathogens ( viz. Vibrio harveyi, Vibrio parahemolyticus, Vibrio vulnificus ) by cross streak method. Saccharopolyspora jiangxiensis IMA1 showed maximum inhibition against aquatic bacterial pathogens. The extract of IMA1 showed maximum inhibition zone of 30 mm against aquatic pathogen, V. parahemolyticus. In addition, the IMA1 extract showed excellent antioxidant activity, significant degree of reducing power and ABTS radical scavenging properties. In vitro anticancer studies showed IC50 values at 16.60 μg/ml in human breast cancer cell lines (MCF-7). The morphological changes were observed at 30 μg/ml. The pharmacologically active metabolites were identified by Gas chromatography–mass spectrometry analysis. It was concluded that the pharmacological activities are dose dependent. The present study shows the potential of IMA1 as promising strain in controlling aquatic bacterial pathogens as well as antioxidant and anticancer properties. Graphical abstract: Image 1 Highlights: Saccharopolyspora sp. IMA1 was isolated from coral reef environment. IMA1 metabolites inhibited V. harveyi, V. parahemolyticus, V. vulnificus . IMA1 extract showed antioxidant and ABTS radical scavenging properties. In vitro anticancer studies showed IC50 values at 16.60 μg/ml in MCF-7 cell lines.